UTILIZATION OF TRADITIONAL ANIMAL PLANTS FOR ANIMAL HUSBANDRY BY MADURASE TRIBE COMMUNITIES IN GRUJUGAN DISTRICT, BONDOWOSO DISTRICT - Iis Nur Asyiah; Adella Ramadhanty; Ika Lia Novenda (BIOEDUKASI, 2020)
The people of Bondowoso Regency are dominated by Madurase, which is 90%. The majority of Madurase in Bondowoso Regency own cattle. The Madurase community is Grujugan Subsdistrict, Bondowoso Regency still maintains ancestral traditions for the care and treatment of cattle, so there is a need for scientific studies on the use of plants for traditional livestock so it will not extinct. The purpose of this study was to determinate the plants used for the care and treatment of cattle, how to process them, the presence of a mixture of other non-plant material in the feed making or traditional medicine of cattle, the types of diseases commonly experienced by cattle, and the types of plants used for cattle feed. This type of research is descriptive exploratory, with a survey method that uses semi-structured interview techniques. The study was conducted in two villages, named Sumber Pandan Village and Wanisodo Village using 18 respondents. The results of the study are inventorying 20 plants species and 14 families that are used for traditional treatment and care of livestock and 9 types of additives use for bleeding in the manufacture of livestock medicine. In addiction there are also 16 species of plants and belong to 8 families that are used for cattle feed by the Madurase Tribe Society in Grujugan District, Bondowoso Regency.